Nitrous oxide content and fluxes in Setúbal Bay, Portugal, during upwelling events - C Gonçalves; MJ Brogueira; MF Camões (Ciencias Marinas, 2011)
To evaluate the influence of upwelling events on nitrous oxide (N2O) levels and sea-air exchange in Setúbal Bay (SW Portugal), measurements of dissolved N2O were carried out from the surface down to 200 m depth in May 2006 and May 2007. During the weak upwelling event (May 2006), higher N2O concentrations (values up to 14 nmol L–1) were observed in the upper and deeper layers. In the upper layers a positive correlation between ΔN2O (N2O excess) and apparent oxygen utilization was calculated, suggesting that nitrification contributed to N2O production. During the stronger upwelling event (May 2007), N2O values were lower and did not surpass 12 nmol L–1. Production of N2O could not be disentangled and apparently upwelling provided an effective pathway for ventilating N2O from subsurface waters to the atmosphere. Surface waters were, in general, supersaturated with respect to the atmosphere (percent saturation values 95–160%), indicating that the study area was acting as a source of atmospheric N2O. Higher upwelling-favorable winds (values up to 9 m s–1) registered in May 2007 contributed to increase N2O emissions, which attained a maximum value of 15.2 µmol m–2 d–1 in this period. Lower N2O sea-air fluxes were estimated in May 2006 and values did not surpass 8.8 µmol m–2 d–1. Taking into account the N2O flux in our study area, the contribution of Portuguese coastal upwelling to N2O emission was estimated, varying from 0.040 to 0.102 Gg N yr–1. These values are lower than those reported for most upwelling systems and represent a minor source to atmospheric N2O.